Juan Medrano service awards - De La Salle University, Manila (Animo Repository, 1995)
Twenty-three members of the different Lasallian schools were conferred the Juan Medrano Service Award during the Eucharistic celebration at the Chapel of the Pearl of Great Price on March 9. The award was given to faculty members or service personnel who have continuously served any Lasallian or La Salle-supervised schools for at least 25 years.